Competitiveness Factors In Smes Of The Gastronomic Sector In Ibagué – Colombia (Journal of Namibian Studies : History Politics Culture, 2022)
The purpose of this paper is to make an analysis of the identifiable factors of competitiveness in the companies of the gastronomic sector in the city of Ibague - Colombia, Competitiveness is measured through a questionnaire designed from a competitiveness map from the Inter-American Development Bank. Variables include quality assurance, human resources, innovation, information and communication technology, accounting and finance were collected.  It´s based on a bibliographic review and a correlational statistical exercise carried out with gastronomic commercial establishments in the city during the months of April to august 2022. The results indicate that on average the firms have a level of competitiveness. This implies opportunities for improvement in all variables, but mainly in human resources.